PERKEMBANGAN PENDIDIKAN KARAKTER YANG DITINJAU MELALUI LITERASI DIGITAL SEBAGAI DASAR UNTUK MENUJU TAHAP REVOLUSI INDUSTRI 5.0 - Sugiarto, Eric Kurniawan (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2026)
This article explains the importance of digital literacy in strengthening character education, especially through citizenship education in the era of Society 5.0. In this era, society needs to combine artificial and social intelligence to face the nation's challenges. Civic education plays an important role at every level of education, aiming to form citizens with strong character. Society 5.0 leverages technology to solve social problems, so students need to have skills such as leadership, digital literacy, emotional intelligence, and global citizenship. Education must teach critical and creative thinking, while still maintaining the values of Pancasila and the 1945 Constitution. In essence, in this era, education needs to balance technological capabilities and character, so that the young generation is ready to face future challenges without forgetting national identity. Character education is an important component that aims to instill moral, ethical, and emotional values in students. In the Society 5.0 Era, which is characterized by the rapid development of digital technology, digital literacy plays a key role in strengthening character education. Digital literacy refers to an individual's ability to understand, use, and actively contribute in a digital environment. This research, which is based on a literature study, analyzes the relationship between digital literacy and character education reinforcement, focusing on aspects such as technological knowledge, digital skills, ethics in the use of digital media, and responsible online behavior. The results of the study show that digital literacy not only helps students master technology, but also develops values such as honesty, responsibility, empathy, cooperation, and problem-solving skills. Thus, digital literacy is one of the effective ways to form positive characters in this modern era.